Processing of co‐reference in autism spectrum disorder. Issue 12 (22nd August 2017) - Howard, Philippa L.; Liversedge, Simon P.; Benson, Valerie
Abstract : Accuracy for reading comprehension and inferencing tasks has previously been reported as reduced for individuals with autism spectrum disorder (ASD), relative to typically developing (TD) controls. In this study, we used an eye movements and reading paradigm to examine whether this difference in performance accuracy is underpinned by differences in the inferential work required to compute a co‐referential link. Participants read two sentences that contained a category noun (e.g., bird ) that was preceded by and co‐referred to an exemplar that was either typical (e.g., pigeon ) or atypical (e.g., penguin ). Both TD and ASD participants showed an effect of typicality for gaze durations upon the category noun, with longer times being observed when the exemplar was atypical, in comparison to typical. No group differences or interactions were detected for target processing, and verbal language proficiency was found to predict general reading and inferential skill. The only difference between groups was that individuals with ASD engaged in more re‐reading than TD participants. These data suggest that readers with ASD do not differ in the efficiency with which they compute anaphoric links on‐line during reading. Autism Res 2017, 10: 1968–1980 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Individuals with autism spectrum disorder (ASD) have previously been reported to have difficulties with reading comprehension. This study examined whether a difference in the speed with which individuals with ASD form connections between words (co‐reference processing) may contribute to comprehension difficulties. No evidence was found to suggest that ASD readers differ to typically developing readers in the speed of co‐reference processing. Therefore, this data would suggest that differences in co‐reference processing are unlikely to account for reading comprehension difficulties in ASD.